Head for business : intermediate student's book - Naunton, Jon. (Oxford : Open University Press, 2000)
This book is about: A common language; Work to live, live to work; Transitions; Company culture; Free to trade; Shopping around; ...
Keywords: English language; Business English; Business communication; English language -- Textbooks for foreign speakers; English language -- Business English